Analysis of Infrastructure, Investment and Human Capital On Economic Growth in Sumatra Provinces 2016–2024 - Putri Ramadhayanti; Farida Rahmawati; Inayati Nuraini Dwiputri (Equivalent : Journal of Economic, Accounting and Management, 2026)
Regional economic growth is an important indicator in assessing the success of regional development. However, inequality in growth between provinces remains a major challenge in Sumatra Island. This research aims to analyze the influence of basic infrastructure, domestic investment, and human capital on economic growth in ten provinces in Sumatra Island for the 2016–2024 period. The basic infrastructure variable is proxied by stable road conditions, access to proper sanitation, and access to proper clean water, while human capital is measured using the Gross Enrollment Ratio for Senior High School (GER SHS). Economic growth is measured using Gross Regional Domestic Product (GRDP) per capita. The analysis method used is panel data regression with a Fixed Effect Model approach, which was chosen based on the results of the Chow test and Hausman test. Estimation results show that access to clean water and Domestic Investment (DI) have a positive and significant effect on economic growth in provinces in Sumatra Island. Meanwhile, stable road conditions show a negative influence at a certain level of significance, while sanitation access and GER SHS do not have a statistically significant effect. These findings indicate that the quality of basic infrastructure and domestic investment have a strategic role in encouraging regional economic growth, although the effectiveness of each infrastructure component differs between provinces. This research provides important policy implications for local governments in determining infrastructure development priorities and investment increase strategies to support more inclusive economic growth in Sumatra Island